Relationship between physical function and sarcopenia in the older adults from Amazonas: A cross-sectional study - Alex Barreto de Lima; Duarte Henrinques-Neto; David Scott; André de Araújo Pinto; Gustavo dos Santos Ribeiro; Miguel Peralta; Kessketlen Alves Miranda; Pedro Campos; Elvio Rúbio Gouveia (PLoS ONE, 2025)
Background Physical functioning refers to the ability to perform daily living activities, namely basic activities, instrumental, and advanced activities. Poorer performance in these areas may indicate the potential presence of sarcopenia. Objectives To analyze the differences in physical function between older people with and without sarcopenia and to investigate the associations between physical function tests and sarcopenia. Methods A cross-sectional study based on data from older people from the Northern region of Brazil in the year 2018 was conducted. Study participants included 312 older people aged ≥  60 years (64.1% female). Sarcopenia was defined using the updated criteria of the European Working Group on Sarcopenia in Older People (EWGSOP2). Physical functioning was measured using functional physical fitness tests (30-second chair stand test, chair sit-and-reach test, 8-foot Up-and-Go Test, 6-minute walk test, 4-meter gait speed, and the Fullerton Advanced Balance Scale). Results Confirmed sarcopenia was detected in 29.2% of participants, but no participant had severe sarcopenia. Most physical function parameters in the crude analysis were associated with confirmed sarcopenia (all p < 0.05), except for the back scratch test. In a model adjusted for sex, age and body mass index, slower 4-meter gait speed (OR = 1.29, 95%CI = 1.08 to 1.54), slower 8-foot up-and-go test time (OR = 1.32, 95%CI = 1.16 to 1.49), greater chair sit-and-reach test (OR = 0.97, 95%CI = 0.94 to 0.99) and higher self-reported Composite Physical Function scores (OR = 0.94, 95%CI = 0.89 to 0.99) were significantly associated with confirmed sarcopenia status. Conclusions EWGSOP2 confirmed sarcopenia is prevalent in older people residing in Brazil’s Northern region and is independently associated with slower walking speed and chair rising ability, reduced trunk and lower-limb flexibility, as well as poorer self-reported physical function.